Variation of ApoL1 Testing Practices for Living Kidney Donors. (March 2020) - McIntosh, Tristan; Mohan, Sumit; Sawinski, Deirdre; Iltis, Ana; DuBois, James M.
Introduction: Tests exist for ApoL1 genetic variants to determine whether a potential donor's kidneys are at increased risk of kidney failure. Variants of the ApoL1 gene associated with increased risk are primarily found in people with West African ancestry. Given uncertainty about clinical implications of ApoL1 test results for living kidney donors and recipients and the lack of uniform guidelines for ApoL1 testing, transplant centers across the United States vary in ApoL1 testing practices. Research Questions: (1) What approach do transplant centers take to determine whether prospective donors are of West African ancestry? (2)How do transplant centers engage potential donors during the ApoL1 testing process? (3) What do transplant centers identify as concerns and barriers to ApoL1 testing? and (4) What actions do transplant centers take when a potential donor has 2 ApoL1 risk variants? Design: We explored the current practices of transplant centers by surveying nephrologists and transplant surgeons at transplant centers evaluating the majority of black living donors in the United States. Results: About half of these transplant centers offered ApoL1 testing. Of those who offered ApoL1 testing, only half involved the donor in decision-making about donation when the donor has 2 risk variants. Discussion: Unaddressed differences in the priorities of transplant centers and black living donors may stigmatize black donors and undermine trust in the health-care and organ donation systems. Variation in transplant center testing practices points to the critical need for further research and community engagement to inform the development of guidelines for ApoL1 testing.